PENGARUH KOMUNIKASI DAN SELEKSI TERHADAP KINERJA KARYAWAN DI PT. BHANDA GHARA REKSA MEDAN - Hendra Nazmi (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
This study is to investigate whether communication skill and recruitment system effect to employee performance. This study is held in the PT. Bhanda Ghara Reksa Medan and involved 61 employees as sample of the study. It is assumed that due to the poor communication among employees some assignments cannot be carried out by the others as expected. Recruitment system is also a factor that causes to job performance when the selected candidates are not in accordance with their educational background or job experiences. This quantitative study is descriptive explorative with questionnaire as an instrument to attain the data and analyzed by multiple linear regression. The data is also processed by using coefficient of determination test simultaneously (F-test) and partial test (t-test). The result indicates that communication skill and selection system in employee recruitment simultaneously and partially have significant effect on employee performance with coefficient of determination value is 0.731. The communication and selection (recruitment) have an effect on employee performance with 73,10% (percentage level), while the rest is 26.90% influenced by other factors that are not examined such as leadership, motivation, and work discipline. Based on the overall results of the study, it is concluded that both communication and selection system effect to employee performance at PT. Bhanda Ghara Reksa Medan